Quantitative role of mast cells in odontogenic cystic enlargement - Shailja Chatterjee; Sumita Mahajan; Karen Boaz; Thomas George (Universidade Estadual de Campinas, 2015)
Aim: Mast cells have been hypothesized to play a significant role in pathogenesis of odontogenic cysts. The aim of this study was to evaluate mast cell distribution in cystic lining and the capsule to formulate a mechanism of cystic expansion. Methods: Ten formalin-fixed paraffin embedded tissue blocks each of OKC, dentigerous and radicular cysts were selected. Toluidine blue staining (1% in 1% NaCl solution) was done in 5µm thick sections and counting performed in 10 areas using an ocular grid. Areas counted were divided into 4 zones: intraepithelial, subepithelial, intermediate and deep zones (Group I, II, III and IV respectively). Statistical analysis: Mean ±S.D. was calculated in each group followed by paired 'T' test. Results: Mast cells had greatest concentration in subepithelial zone. 'T' test showed no significant differences between group I and II zones in OKC but a highly significant difference between groups I and II in dentigerous cyst. Radicular cysts showed a significant difference between groups II and III. Conclusion: Mast cell degranulation releases numerous hydrolytic enzymes that facilitate breakdown of capsular matrix increasing the hydrostatic pressure due to raised osmolality. Influx of tissue fluids results in their enlargement coupled with resorption at the bone-cyst interface.